Altered Growth and Wood Characteristics in Transgenic Hybrid Aspen Expressing Agrobacterium tumefaciens T-DNA Indoleacetic Acid-Biosynthetic Genes. - Tuominen, H. (1995)
A key regulator of cambial growth is the plant hormone indoleacetic acid (IAA). Here we report on altered wood characteristics and growth patterns in transgenic hybrid aspen (Populus tremula L. x Populus tremuloides Michx.) expressing Agrobacterium tumefaciens T-DNA IAA-biosynthetic iaaM and iaaH genes. Eighteen lines simultaneously expressing both genes were regenerated. Of these, four lines, verified to be transgenic by northern blot analysis, were selected and raised under controlled growth conditions. All four lines were affected in their growth patterns, including alterations in height and stem diameter growth, internode elongation, leaf enlargement, and degree of apical dominance. Two transgenic lines, showing the most distinct phenotypic deviation from the wild type, were characterized in more detail for free and conjugated IAA levels and for wood characteristics. Both lines showed an altered IAA balance, particularly in mature leaves and roots where IAA levels were elevated. They also exhibited changes in wood anatomy, most notably a reduction in vessel size, an increase in vessel density, and changes in ray development. Thus, the recent development of techniques for gene transfer to forest trees enabled us to investigate the influence of an altered IAA balance on xylem development in an intact experimental system. In addition, the results demonstrate the possibility of manipulating wood properties in a forest tree through controlled changes of IAA concentration and distribution.